Time Intervals Under the Lens at Sweden’s First Diagnostic Center for Primary Care Patients With Nonspecific Symptoms of Cancer. A Comparison With Matched Control Patients - Sundquist, Jan; Palmér, Karolina; Rydén, Stefan; Sävblom, Charlotta; Ji, Jianguang; Stenman, Emelie (Frontiers in Oncology, 2020)
Introduction: Fast-track referral pathways for patients with nonspecific, serious symptoms have been implemented in several countries. Our objective was to analyze time intervals in the diagnostic routes of patients diagnosed with cancer at Sweden’s first Diagnostic Center (DC) for nonspecific symptoms and compare with time intervals of matched control patients. Methods: Adult patients with nonspecific symptoms that could not be explained by an initial investigation in primary care were eligible for referral to the DC. Patients diagnosed with cancer were matched with patients at another hospital within the same healthcare organization. We aimed for two control patients per DC-patient and matched on tumor type, age and sex. Five time intervals were compared: 1) patient interval (first symptom – primary care contact), 2) primary care interval (first visit – referral to the DC/secondary care), 3) diagnostic interval (first visit – cancer diagnosis), 4) information interval (cancer diagnosis – patient informed) and 5) treatment interval (cancer diagnosis – treatment start). Comparisons between groups and matched cohort analyses were made. Results: 64 patients (22.1%) were diagnosed with cancer at the DC, of which eight were not matchable. 42 patients were matched with two controls and 14 were matched with one control. There were no significant differences in patient-, primary care- or diagnostic intervals between the groups. The information interval was shorter at the DC compared to the control group (difference between matched pairs 7 days, p = 0.001) and the treatment interval was also shorter at the DC with significant differences in the matched analysis (difference between matched pairs 13 days, p = 0.049). The findings remained the same in four sensitivity analyses, made to compensate for differences between the groups. Conclusions: Up to diagnosis, we could not detect significant differences in time intervals between the DC and the control group. However, the shorter information and treatment intervals at the DC should be advantageous for these patients who will get timely access to treatment or palliative care. Due to limitations regarding comparability between the groups, the results must be interpreted with caution and further research is warranted. ClinicalTrials.gov-ID: NCT01709539. Registration-date: October 18, 2012.